PERENCANAAN PENGEMBANGAN ASET TAMAN TEMATIK BERDASARKAN SMART CITY PARK DI TAMAN TONGKENG KOTA BANDUNG - Dewi Purnama, Putri; Shafa Zahirah, Afifah (Unitri Press, 2024)
This project aims to produce a thematic park asset development plan based on the smart city park in Taman Tongkeng which consists of Facilities, Water, Green Space, Paving Roadway, and Users as well as an estimate of the costs required to implement the project process. This project uses descriptive methods with qualitative and quantitative approaches. Data collection is based on the results of observations, interviews, documentation studies and benchmarking. This project produces asset development planning with a smart city park concept which consists of a Facility dimension in the form of planning 6 facilities, namely the Water Dimension in the form of planning automatic sprinklers. The Green Space dimension is in the form of bio-swales technology planning. Paving Roadway dimensions in the form of smart parking and ramp planning. The Users dimension is WIFI planning. The estimated cost for this project is IDR 206,363,927,525 which consists of demolition, construction and procurement costs. This project requires a review of the project cost budget, creation of a DED, and analysis of the maintenance required by the park.